The value of the analysis of the urinary stones for studying the features of urolithiasis pathogenesis - D. G. Lebedev; V. I. Smirnova; S. V. Lapin; O. O. Burlaka; E. V. Rozengauz; V. L. Emanuel (Вестник урологии, 2021)
Introduction. Urolithiasis is a multifactorial recurrent disease, unevenly spread throughout the world and characterizedby the formation of urinary stones of various chemical compositions, depending on pathogenesis, etiological, and epidemiological risk factors. Understanding the composition of chemicals and their prevailing ratios can help make decisions about treatment tactics, preventive measures to reduce the risk of recurrence and the prevalence of urolithiasis.Purpose of the study. To assess the distribution of chemical components in urinary stones along with an analysis of their population significance.Materials and methods. The urinary stones were obtained from 2854 patients with urolithiasis. The composition of urinary stones was analyzed by using an infrared spectroscopy method.Results. The predominance of oxalate stones was determined in multicomponent kidney stones (83,7%) and the prevalence of urate stones (54,2%) was revealed in monocomponent kidney stones. Urinary stones with a predominance of oxalates contained significantly fewer impurities (12.4%) than urinary stones with a predominance of urates, phosphates and carbonates with an average amount of impurities >24.0%.Conclusion. The analysis of urinary stones distribution based on pathogenic factors showed that the calcium metabolism disturbances prevail in the population of the Russian Federation (88.0%).